2009
DOI: 10.1002/pro.200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the variable domain of the Streptococcus gordonii surface protein SspB

Abstract: The Antigen I/II (AgI/II) family of proteins are cell wall anchored adhesins expressed on the surface of oral streptococci. The AgI/II proteins interact with molecules on other bacteria, on the surface of host cells, and with salivary proteins. Streptococcus gordonii is a commensal bacterium, and one of the primary colonizers that initiate the formation of the oral biofilm. S. gordonii expresses two AgI/II proteins, SspA and SspB that are closely related. One of the domains of SspB, called the variable (V-) do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 38 publications
(49 reference statements)
0
34
0
Order By: Relevance
“…BspA-V adopts a fold that is distinct from those reported for other AgI/II family polypeptide V domains (11,12). This consists of two anti-parallel ␤-sheets, S1 and S2, comprising 5 and 7 strands, respectively (Fig.…”
Section: The Bspa Variable Domain Possesses a ␤-Sandwich Fold That Ismentioning
confidence: 90%
See 1 more Smart Citation
“…BspA-V adopts a fold that is distinct from those reported for other AgI/II family polypeptide V domains (11,12). This consists of two anti-parallel ␤-sheets, S1 and S2, comprising 5 and 7 strands, respectively (Fig.…”
Section: The Bspa Variable Domain Possesses a ␤-Sandwich Fold That Ismentioning
confidence: 90%
“…The N terminus forms a stabilizing scaffold by wrapping behind the base of the stalk (10). Crystal structures of the V regions of SpaP and SspB have revealed a common architecture consisting of a lectin-like fold with a putative binding cleft (11,12). The structure of the C-terminal subdomains C1, C2, and C3 has also been elucidated by x-ray crystallography and found to consist of ␤-sandwich domains stabilized by isopeptide bonds (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Interestingly, the SspB polypeptide sequence also contains three potential ␤-aggregation sequences, predicted by the TANGO algorithm (15). One of these (742 to 746 amino acids [aa]) is within the central V region of the protein and, on the basis of the three-dimensional (3D) crystal structure (4), is predicted to be at the opening of the receptor-binding pocket (16). It remains to be determined if these self-propagating sequences are involved in interactions of Als3p with SspB.…”
Section: Discussionmentioning
confidence: 99%
“…1). Highresolution crystallography of the C-region of S. gordonii SspB (Forsgren et al, 2009) showed this to form two distinct domains, each containing a covalent isopeptide bond between a lysine and an asparagine residue. Such intra-molecular cross-links have been reported in Gram-positive bacterial pili (Kang et al, 2007) and are thought to stabilize elongated structures, potentially enabling streptococci to better resist detachment from oral surfaces.…”
Section: Antigen I/ii Family Polypeptidesmentioning
confidence: 99%